Cuidado Humanizado en el Parto Distócico: A propósito de Un Caso. - Espinoza Lambert, Cristhian Patricio; Calmet Gallegos, Angie Karelis (My University, 2024)
Dystocic labor is an alteration in the normal progression of labor, frequently associated with anatomical, functional, or fetal factors, and represents a significant risk to maternal and perinatal health. The objective of this study was to identify risk factors and complications in an elderly patient diagnosed with dystocic labor, through the implementation of an individualized and humanized care plan. This was a qualitative, descriptive-analytical study based on a review of medical records, direct observation, and the application of ethical and bioethical criteria. The patient, a 39-year-old primigravida at 41.1 weeks' gestation, was admitted with a diagnosis of obstructed labor due to pelvic stricture and triple loop of the cord. An emergency cesarean section was performed, resulting in a live birth with an Apgar score of 8/9 and no immediate neonatal complications. During the postoperative period, mild anemia was identified, which was treated with parenteral iron. Nursing care included continuous monitoring of vital signs, infection prevention, breastfeeding education, and emotional support. The theoretical basis for the care was Betty Neuman's Systems Model, which allowed for the identification of physiological and emotional stressors, promoting timely and effective interventions. This theory facilitated a holistic approach that contributed to preserving the stability of the patient's system in the face of the stress of the obstetric event. The findings highlight the importance of providing humane, person-centered care, emphasizing patient safety, effective communication, and professional support as essential elements for optimizing maternal and neonatal health outcomes.
El parto distócico es una alteración en el progreso normal del trabajo de parto, frecuentemente asociada a factores anatómicos, funcionales o fetales, y representa un riesgo significativo para la salud materna y perinatal. El objetivo de este estudio fue identificar los factores de riesgo y complicaciones en una paciente añosa con diagnóstico de parto distócico, mediante la aplicación de un plan de cuidados individualizado y humanizado. Se trató de una investigación cualitativa, de tipo descriptivo-analítico, basada en la revisión de historia clínica, observación directa y aplicación de criterios éticos y bioéticos. La paciente, primigesta de 39 años con 41,1 semanas de gestación, ingresó con el diagnóstico de trabajo de parto obstruido por estrechez pélvicay triple circular de cordón. Se practicó cesárea de emergencia, obteniéndose un recién nacido vivo, con puntuación Apgar 8/9 y sin complicaciones neonatales inmediatas. Durante el posoperatorio, se identificó anemia leve, tratada con hierro parenteral. Elcuidado de enfermería incluyó monitoreo continuo de signos vitales, prevención de infecciones, educación en lactancia y apoyo emocional. Se utilizó como base teórica el Modelo de Sistemas de Betty Neuman, el cual permitió identificar estresores fisiológicos y emocionales, favoreciendo intervenciones oportunas y efectivas. Esta teoría facilitó un abordaje holístico que contribuyó a preservar la estabilidad del sistema de la paciente frente al estrés del evento obstétrico. Los hallazgos resaltan la importancia de brindar un cuidado humanizado centrado en la persona, enfatizando la seguridad del paciente, la comunicación efectiva y el acompañamiento profesional como elementos esenciales para optimizar los resultados en la salud materna y neonatal.
Keywords: PARTO DISTÓCICO; CUIDADO DE ENFERMERÍA; TEORIA DE BETTY NEUMAN; MATERNIDAD A EDAD AVANZADA